Anatomical variations and pathological changes in the hearts of free-ranging Eurasian lynx (Lynx lynx) in Finland - Kareinen, Ilona; Lavonen, Emilia; Viranta-Kovanen, Suvi; Holmala, Katja; Laakkonen, Juha (European Journal of Wildlife Research, 2020)
The Eurasian lynx (Lynx lynx) despite the wide distribution has fragmented populations with possibly decreased genetic variability. Reports from Central Europe have raised cardiac health as possible risk factor for lynx populations. The knowledge on normal anatomic variations of lynx heart is crucial to assess emerging pathological or hereditary disorders. The aim of this study was to give a detailed description of the cardiac anatomy and circulation of the Eurasian lynx and to report the cardiac health of the lynx in Finland. The cardiac anatomy and pathology were studied post mortem from 63 legally hunted lynx. In general, the cardiac anatomy of Eurasian lynx corresponded with that described for other felids. In the ventricles, varying number of thin ventricular bands was a common feature and their histological appearance was characterized by a fibromuscular pattern. The size of the heart varied between males and females, but the relative size was similar to that described for most domesticated carnivores. No marked pathologic lesions were observed in the lynx hearts. Fibrosis was observed in 56% of the hearts, but it was focal and mild in degree and unlikely to affect cardiac function or to have clinical significance. In conclusion, the cardiac health of the Finnish Eurasian lynx population is good with no signs of heritable cardiac disorders. Furthermore, we were able to give a detailed anatomic description of the lynx heart, which can serve as a reference for further epidemiological investigations on cardiac diseases in lynx populations. Peer reviewed